1988
DOI: 10.1037/0022-3514.55.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Source expertise, source attractiveness, and the processing of persuasive information: A functional approach.

Abstract: Male undergraduates high and low in self-monitoring listened to either an expert or attractive male source deliver a counterattitudinal message supported by either strong or weak arguments. As expected, high self-monitoring individuals agreed with the expert source regardless of the quality of the arguments presented but agreed with the attractive source only when he delivered strong arguments. By contrast, low self-monitoring individuals agreed with the attractive source regardless of the quality of the argum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
1
9

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(163 citation statements)
references
References 21 publications
(38 reference statements)
8
144
1
9
Order By: Relevance
“…Indeed, previous research has consistently shown that persuasive arguments have a greater impact when they target a recipient's chronic or temporary motivations (e.g. DeBono, 1987;DeBono & Harnish, 1988;Lavine & Snyder, 1996;Petty & Wegener, 1998;Prentice, 1987;Shavitt, 1990). Furthermore, previous research has also shown that persuasive communications benefit from matching their targets' regulatory focus (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research has consistently shown that persuasive arguments have a greater impact when they target a recipient's chronic or temporary motivations (e.g. DeBono, 1987;DeBono & Harnish, 1988;Lavine & Snyder, 1996;Petty & Wegener, 1998;Prentice, 1987;Shavitt, 1990). Furthermore, previous research has also shown that persuasive communications benefit from matching their targets' regulatory focus (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Este modelo de cambio actitudinal permite, entonces, controlar y predecir resultados específicos para las diferentes variables persuasivas como, por ejemplo, aquellas relativas al emisor (e.g., el atractivo; DeBono & Harnish, 1988), al receptor (e.g., el estado de ánimo; Briñol, Petty & Barden, 2007), al canal (e.g., escrito; Burnkrant & Howard, 1984) o al mensaje (e.g., que contiene o no preguntas retóricas; Petty, Cacioppo et al, 1981).…”
Section: Cambio De Actitudesunclassified
“…This can happen via sounds, words, graphics, and many other forms of media. Dialog support has been robustly shown to influence the persuasiveness of systems (e.g., Cable and Judge, 2003;DeBongo and Harnish, 1988;Enns et al, 2003 ;Petty et al, 1993 ;Schweidel et al, 2006 ;Westphal and Stern, 2007). This increase in persuasion is a function of people subconsciously asking themselves "how they feel about the message," and in doing so they attribute the positive affect to their judgment of confidence (Forgas, 1995 ;Schwarz and Clore, 1983 ).…”
Section: Dialogue Supportmentioning
confidence: 99%
“…This degree of credibility can be influenced by the system's appearance, real-world feel, and surface credibility (Angst and Agarwal, 2009;DeBongo and Harnish, 1988 ). This occurs because positive credibility "primes" other positive thoughts in the brain, making them easier to recall, thus influencing a user's judgment (Bower, 1981).…”
Section: System Credibility Supportmentioning
confidence: 99%